Megalops atlanticus Valenciennes, 1847 (Elopiformes, Megalopidae): New records for the state of São Paulo, with comments on its occurrence in the southeastern coast of Brazil, Southwest Atlantic - Garrone-Neto, Domingos [UNESP]; Rodrigues, Alexandre [UNESP] (Pensoft Publishers, 2018)
New records of Megalops atlanticus Valenciennes, 1847 in the state of São Paulo, southeastern Brazil, are reported from recreational catches carried out in February 2017. Data collected is the first occurrence of this species in more than 50 years, extending its geographic distribution by about 250 km, from Cananéia, in the south, to Guarujá, on the central coast. Although rarely recorded, M. atlanticus is present off the coast of São Paulo. This possibly represents the southernmost distribution for M. atlanticus in the Southwest Atlantic.
Keywords: Citizen science; Conservation; Geographical distribution; Recreational fishing; Tarpon; Wide-ranging species